Penurunan Tekanan Darah Penderita Hipertensi Setelah Diberikan Terapi Akupresur (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Hypertension or high blood pressure is one of the silent killers among other killers. A preliminary study found that 7 out of 11 who suffer from hypertension have done massage on the head, neck, shoulders, and back. However, sufferers say doing massage to reduce headaches without knowing which point should be pressed for hypertension. This study aimed to determine the effect of acupressure therapy on reducing blood pressure in hypertension patients in the working area of ​​Mamboro Health Center. This study's design was an analytic study using pre-experiments with one group pre and post-test design. The number of samples in this study was 7 respondents who were calculated using the formula of Lemeshow. The sampling technique was purposive sampling. The data analysis used univariate analysis and bivariate analysis with paired t-tets as a statistical test. The results showed that the distribution of blood pressure frequency of respondents after acupressure therapy from 7 respondents there were 5 people (71.42%) decreased, and 2 people (28.58%) remained. This study concludes that acupressure therapy affects the reduction of blood pressure in hypertension patients. Suggestions for Mamboro Public Health Centers, these results can be used as input in setting a policy to implement complementary therapy for hypertension patients.